An effective edge conductivity for reducing staircasing error in induced electric field computation for low-frequency magnetic field dosimetry. (7th November 2022) - Diao, Yinliang; Zhang, Lianlong; Shi, Dan; Hirata, Akimasa
Abstract: Objective. In the low-frequency exposure (<100 kHz), the induced electric field strength is used as a metric for assessment for human protection. Unlike radio-frequency exposure (>MHz), the computational assessment suffers from staircasing error in biological objects. The international guidelines consider additional reduction factor of 3 when setting the limit. Here we propose a new method to reduce the staircasing error in the skin for low-frequency magnetic field dosimetry of voxelized body models. Approach . We have proposed a new method considering the filling ratio of the skin tissue to the air–skin and skin–fat interfaces to determine an effective conductivity for each voxel edge. The proposed method was applied to voxel head models exposed to a uniform magnetic field at 50 Hz. After validation using layered spherical models with several resolutions, anatomical head models are used for further verification. Main results. A comparison of maximum electric field strengths with analytic solutions in two-layer sphere models suggested that the differences in the proposed approach were less than 5.6%, which was smaller than those without the proposal of 26.7%. The distribution of the skin electric field become smoother using the proposed approach, and the staircasing effects were almost unobservable from the field distributions. Significance. The proposed method suggests vital implications for determining induced electric fields in the skin, which is needed to set the limit for human protection from low-frequency electromagnetic fields. The method would be useful when setting the reduction factor and limit in the exposure guidelines and standard.